Innovations in the Portuguese local government: independent lists and citizen participation, mayors' limited terms and the parity law - Almeida, Maria Antónia (IPSA Lisboa, 26th World Congress of Political Science, 2021)
The democratic regime has introduced administrative decentralization in Portugal. After over four decades of regular elections and party competition there were several conquests in local government, but there was also a negative image associated with longevity and corruption and a huge decrease in voters’ turnout. Two important legal innovations have since been introduced, which might improve citizen participation and the quality of local democracy in Portugal: mayors’ terms were limited to three (twelve years maximum in office, applied since the 2013 elections) and independent local lists were allowed to enter the race in the form of citizen groups. The first measure has brought some rejuvenation in local government. The introduction of citizen groups, in a political party strong environment, had been a negligible factor since its first result in 2001, when only 0.6 per cent of mayors were elected outside the party system. However, since 2013 this new political force is a growing trend, which now occupies a honourable fourth place in local elections. But are local lists innovative in citizen participation? Are they a positive contribution for the improvement of representative democracy? Independent mayors’ sociological and political paths are analysed in order to show their actual independence, as well as turnout results. Do they actually provide a different approach to local government, particularly regarding voters who are unsatisfied with the democratic process? Other innovations are also analysed, such as the parity law, participative budgets and decentralized local council meetings, which have provided new tools for citizen participation.